Small bowel intussusception from renal cell carcinoma metastasis: a case report and review of the literature. (December 2016) - Bellio, Gabriele; Cipolat Mis, Tommaso; Kaso, Gladiola; Dattola, Roberto; Casagranda, Biagio; Bortul, Marina
Abstract Background Renal cell carcinoma is the most frequent malignant neoplasia of the kidney accounting for 90 % of all renal solid tumors. Metastases from renal cell carcinoma are rarely located in the small bowel and generally their clinical presentation includes bleeding and obstruction. Intussusception in adults is an extremely rare pathological condition and only 30 to 35 % of small bowel intussusceptions are derived from malignant lesions. Case presentation We report here a clinical case of a 75-year-old white man hospitalized for anemia and subocclusion. An abdominal ultrasound and computed tomography showed a small bowel intussusception. During a surgical exploration, a polypoid lesion was found to be the lead point of the intussusception. His small intestine was resected and a functional side-to-side anastomosis was performed. The histological features of the surgical specimen confirmed the diagnosis of metastatic renal cell carcinoma. Conclusions Small bowel intussusception from renal cell carcinoma metastasis should always be considered in the setting of unexplained intestinal subocclusion in patients with a history of renal cell carcinoma.